2014
DOI: 10.1530/rep-13-0499
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality trends in French regions are consistent with a global change in environmental exposure

Abstract: A retrospective study carried out recently in a large sample of men, close to the general population, has reported a significant and strong decline in sperm concentration and morphology in the whole of France between 1989 and 2005. We studied these trends within each region of France. Data were obtained from the Fivnat database. The study sample comprised male partners of sterile women in whom both tubes were absent or blocked. They were located at the assisted reproductive technology center. A Bayesian spatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…For example, a comprehensive analysis in 2000 of data from more than 100 studies in Western countries provided evidence of a decline in human spermatogenesis during the preceding 50 years [1]. More recent longitudinal cross-sectional studies suggest reductions in both sperm count and quality among young men (ages 18–37) in China (2001–2015;[2]), Spain (2001–2011;[3]), France (1989–2005;[4]), Denmark (1996–2010;[5]), and Finland (1998–2006; [6]). Changes in sperm production have coincided with increases in the incidence of other reproductive defects, including hypospadias, cryptorchidism, and testicular germ cell cancers (reviewed in [7]), and the combined spectrum of reproductive effects has been termed testicular dysgenesis syndrome (TDS; [8]).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a comprehensive analysis in 2000 of data from more than 100 studies in Western countries provided evidence of a decline in human spermatogenesis during the preceding 50 years [1]. More recent longitudinal cross-sectional studies suggest reductions in both sperm count and quality among young men (ages 18–37) in China (2001–2015;[2]), Spain (2001–2011;[3]), France (1989–2005;[4]), Denmark (1996–2010;[5]), and Finland (1998–2006; [6]). Changes in sperm production have coincided with increases in the incidence of other reproductive defects, including hypospadias, cryptorchidism, and testicular germ cell cancers (reviewed in [7]), and the combined spectrum of reproductive effects has been termed testicular dysgenesis syndrome (TDS; [8]).…”
Section: Introductionmentioning
confidence: 99%
“…A recent work showed that sperm concentration in France has been declining by 1.9% per year from 1996 to 2005 (23). It is now generally admitted that, despite geographic variations in semen quality, a global decrease in sperm count has occurred over the past five decades (24). Moreover, the incidence of testicular cancer, which is the most prevalent cancer in young men, has been steadily increasing in all studied countries.…”
Section: Fetal Testis Is a Major Target Of Endocrine Disruptorsmentioning
confidence: 99%
“…Reduced semen quality was observed in semirural and agricultural areas, the highest median sperm count being in the state of New York with zero agriculture surfaces. A study on male partners of infertile women consulting fertility clinics in France showed that the lowest sperm concentrations were in regions with high agricultural surfaces (Le Moal et al ., ). These studies highlighted the importance of environmental factors, but a potential selection bias in the choice of the study population was often discussed whereby results were thought not to necessarily reflect the situation in the general population (Muller et al ., ; Hauser et al ., ; Deonandan & Jaleel, ).…”
Section: Introductionmentioning
confidence: 97%